Analysis of Factors Causing the Prevalence of Child Marriage in Majene Regency - Yasim, Sulastri; Muh. Chaerul Anwar (Alauddin Law Development Journal (ALDEV), 2024)
The fact that child marriages occurred in the territory of Majene district increased the prevalence of child marriages. The method used was normative way. The findings showed that the child, as the golden generation and successor of the nation, has the right to survive, grow and develop, and to participate optimally in accordance with the dignity and dignity of humanity, to be protected from violence and discrimination. Therefore, the study aims to analyze the causes and prevention efforts of the prevalence of child marriage in the district. The type of research used is empirical law research which consists of research into the identification and effectiveness of law. The results of the study showed that there were 20 (twenty) applications for marriage dispensation cases registered with the Majene Religious Court in the period from January to August 2023.